CALL and Complexity – Short Papers From EUROCALL 2019 2019
DOI: 10.14705/rpnet.2019.38.1039
|View full text |Cite
|
Sign up to set email alerts
|

Defining teachers’ readiness for online language teaching: toward a unified framework

Abstract: As part of a larger effort to support Less Commonly Taught Languages (LCTL) instruction in the United States, the LCTL Partnership at Michigan State University (MSU) and the LCTL Collaborative Partners initiative at the University of Chicago (UC) are supporting online LCTL courses to be offered to students across multiple institutions. As the initiatives were underway, it became clear that LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Next, the pedagogical skills refer to knowledge and ability to conduct and facilitate teaching and learning activities. Lastly, the evaluative skills refer to the analytical ability to assess the tasks and overall course and make necessary modifications to ensure language learning objectives are met" (Compton, 2009, p. 81) In their study, Van Gorp et al (2019) further organized each skill domain into four levels of expertise: limited, novice, proficient and expert. See Table 1 for description: Baran et al (2011) in their metaanalysis report that the importance placed on the online teachers' roles and competencies varies as it is context-dependent (i.e.…”
Section: Bridging the Digital Dividementioning
confidence: 99%
“…Next, the pedagogical skills refer to knowledge and ability to conduct and facilitate teaching and learning activities. Lastly, the evaluative skills refer to the analytical ability to assess the tasks and overall course and make necessary modifications to ensure language learning objectives are met" (Compton, 2009, p. 81) In their study, Van Gorp et al (2019) further organized each skill domain into four levels of expertise: limited, novice, proficient and expert. See Table 1 for description: Baran et al (2011) in their metaanalysis report that the importance placed on the online teachers' roles and competencies varies as it is context-dependent (i.e.…”
Section: Bridging the Digital Dividementioning
confidence: 99%
“…WL teachers' human capital during COVID-19 has not been explicitly studied. However, scholars suggest that most language educators have neither taught online nor experienced a language course through that medium (Moser et al, 2021;Van Gorp et al, 2019). In their study of language teachers in the United States, Moser et al (2021) found that only 15% reported prior experiences with online instruction.…”
Section: Preparation For Online Contexts and Human Capitalmentioning
confidence: 99%
“…Online teaching readiness is related to a multitude of factors and dimensions that range from technical, organisational and social (see Cutri and Mena, 2020; Hung, 2016; Van Gorp et al , 2019). Chi (2015) conceptualised readiness as consisting of categories of faculty and technology support, social and student engagement, evaluation and assessment factors and course development and instructional design.…”
Section: Literature Reviewmentioning
confidence: 99%